1990
DOI: 10.1145/93548.93568
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation and evaluation of the FNC-2 attribute grammar system

Abstract: FNC-2 is a new attribute grammar processing system aiming at expressive power, efficiency, ease of use and versatility.Its development at INRIA started in 1986, and a first running prototype is available since early 1989. Its most important features are: efficient exhaustive and incremental visit-sequence-based evaluation of strongly (absolutely) non-circular AGs; extensive space optimizations; a specially-designed AG-description language, with provisions for true modularity;portability and versatility of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Although YACC is widely accepted as a valuable tool for the specification of syntax rules and parsing, it has been shown that its use is restrictive for AGs [21] (e.g., it does not support inherited attributes). Several other attribute grammar evaluators also do exist (following the conventional approach) defining an AG-like syntax such as ELI [21] and FNC2 [9]. Those systems also allow the specification of blocks of sequential code within the attribute evaluation rules.…”
Section: The Extended C Language (C-ag)mentioning
confidence: 99%
“…Although YACC is widely accepted as a valuable tool for the specification of syntax rules and parsing, it has been shown that its use is restrictive for AGs [21] (e.g., it does not support inherited attributes). Several other attribute grammar evaluators also do exist (following the conventional approach) defining an AG-like syntax such as ELI [21] and FNC2 [9]. Those systems also allow the specification of blocks of sequential code within the attribute evaluation rules.…”
Section: The Extended C Language (C-ag)mentioning
confidence: 99%
“…How we achieve both efficiency and expressive power has to do with the evaluation methods; ours are described in detail elsewhere [Par88, JPJ90,JuP90]. However, as far as programming and developing applications are concerned, this does not matter much, provided of course that the system does a reasonable job in implementing the specification.…”
Section: G E N E R a L O V E R V I E Wmentioning
confidence: 99%
“…It aims at production-quality by providing efficiency, expressive power, ease of use and versatility. To achieve these qualities, it uses the latest results in AG implementation [JPJ90], which it combines with OLGA, a new language especially designed for the specification of AGs [JLP90].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it appears that this is not yet the case, although AGs have been around for quite a long time and although powerful AG-processing systems are now available (e.g., FNC-2 [9], which is the base of the present work; see also [1] for a good list of other systems). In our opinion, the main reason for this is that AGs still cruelly lack the same support for modularity as the one which is offered by most programming languages, even the oldest ones [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our system based on Strongly Non-Circular (SNC) attribute grammars [9], this construction looses a bit of power because the SNC class is not closed under descriptional composition [6]: the attribute grammar resulting from the descriptional composition of SNC modules is not necessarily SNC. Moreover, in the context of attribute grammar reuse [3], descriptional composition appeared to be limited due to the need for complete reconstruction of the resulting attribute grammar before any evaluator construction: separate compilation is impossible.…”
Section: Introductionmentioning
confidence: 99%